Evaluation of the anti-oxidant, anti-microbial, antibiofilm potential of biosurfactants derived from Pediococcus pentosaceus S-2 - Kaundal, Tamanna; Batra, Navneet; Sharma, Anjali (Asia-Pacific Journal of Science and Technology, 2025)
Numerous Lactic acid bacteria (LAB) tend to produce different types of biosurfactants i.e surface-active compounds. In the current investigation, biosurfactants derived from Pediococcus pentosaceus S-2 were explored for anti-oxidant, antimicrobial and antibiofilm activities against different test microorganisms. Pediococcus pentosaceus S-2 derived biosurfactants exhibited radical scavenging activity and antioxidant activity of 71% at a concentration of 600 µg. Antimicrobial activity was observed against different micro-organisms in the range between 0.8-5 mg/mL. At 4X minimum inhibitory concentration (MIC), there was 59-65 % inhibition of microbial biofilms in the presence of biosurfactants. Additionally, search engine marketing (SEM) microscopy provided additional evidence of the dispersion of different microbial biofilms in the presence of biosurfactants. Moreover, the biosurfactants also led to a reduction in the content of extracellular polymeric substances (EPSs), including proteins and carbohydrates, further contributing to the mitigation of microbial biofilms. These findings underscore the multifaceted potential of biosurfactants derived from Pediococcus pentosaceus S-2, suggesting their promising role as alternatives to synthetic surfactants across various applications, including antimicrobial, antibiofilm, and antioxidant functions.